Evaluation Of Psychological Distress, Emotional Burnout Symptoms And Perceived Barriers To Seek Professional Help Among Healthcare Professionals In Kuala Lumpur Hospital - Lee, Lenny Cheann (2018)
The level of psychological distress and emotional burnout is high worldwide among the healthcare professionals working in a hospital setting and this occurrence may impact professional productivity, patient satisfaction, mental health and medical errors. The objectives of this study are to: (1) evaluate the prevalence and factors associated with psychological distress and emotional burnout among healthcare professionals, and (2) explore the perceived barriers to seek for professional psychological help by healthcare professionals working in a tertiary public hospital. A sequential two-phase research design was used to achieve the objectives. In Phase I of the study, BDI (Beck Depression Inventory), BAI (Beck Anxiety Inventory), and the MBI-HSS (Maslach Burnout Inventory – Human Service Survey) were used in a cross-sectional questionnaire survey. In Phase II, a qualitative study using semi-structured and individual in-depth interviews was conducted. The questionnaire was completed by 277 healthcare professionals who comprise of doctors and pharmacists. Findings from phase I show that healthcare professionals are experiencing prevalence of emotional burnout 33.6% (95% CI: 28.0 - 39.0) and depressive 14.4% (95% CI: 10.0 - 19.0) symptoms. The prevalence of anxiety symptoms was 6.1% (95% CI: 3.0 - 9.0).